Complex approach to the problem of increasing the reliability of airborne radio equip¬ment - Зубарев, В. В.; Ленков, C. B. (Proceedings of National Aviation University (archive), 1999)
Considered is a new approach to the problem of increasing the reliability of a newly developed airborne radioelectronic equipment at all stages of life cycle. It is proposed to use "balancing technology" of control